Successful restaurant management : from vision to execution - Wade, Donald (Australia : Thomson Delmar Learning, 2006)
[This text] is designed for future restaurant owners or managers who need to learn every aspect of operating a restaurant business. [The text] provides information on such key topics as site selection, construction and design, menu engineering and development, sanitation management, finance, marketing, human resource management, and more ... This in-depth, all-inclusive book includes everything a new restaurant manger needs to learn and know to finance, open, and operate a successful restaurant.
Introduction to the restaurant business -- Menu design and engineering -- Marketing, research analysis and building a customer base -- Site selection -- Business plan -- Finance and accounting -- Building the restaurant -- Sanitation management -- Operations and analysis -- Customer service -- Human resource management --
Includes index.
Keywords: RESTAURANT MANAGEMENT